The Mechanical Lateral Distal Femoral Angle in Thai Patients With Varus Knee Osteoarthritis - Ketwongwiriya, Sittipong; Chotanaphuti, Tanai; Thongsukkaeo, Sitthirat; Khuangsirikul, Saradej; Chotanaphuti, Thanainit (Journal of Southeast Asian Orthopaedics, 2025)
Purpose: Varus deformity is commonly observed in knee osteoarthritis (OA) and involves medial compartment degeneration, bone morphologic changes, soft tissue balance, and may complicate mechanical alignment during total knee arthroplasty (TKA), especially involving conventional alignment techniques. We evaluated the distribution of mechanical lateral distal femoral angle (mLDFA) and its association with coronal alignment parameters in Thai patients with varus knee OA to improve preoperative planning. Methods: Patients with varus knee OA who underwent preoperative orthoroentgenographic imaging between 2020 and 2023 were retrospectively stratified into three mLDFA-based groups (<90° [A], 90° [B], >90° [C]) to compare differences in hip-knee-ankle angle (HKAA), joint line convergence angle (JLCA), and mechanically aligned-anatomical angle (MA-AA). Results: mLDFA prevalence was determined in 444 patients (Group-wise: A=56.3%; B=28.7%; C=14.9%). Group A had smaller MA-AA values (5.38° ± 1.44°) compared with Group C (6.74° ± 1.69°, p < 0.001). Increased mLDFA values were associated with reduced HKAA values, while mLDFA values positively correlated with those of MA-AA. The mean JLCA value was significantly higher in patients with HKAA <170° compared with those with HKAA ≥170° (7.14° vs. 3.83°, p < 0.001). A JLCA value ≥10° was more prevalent in patients with HKAA <170° (18.2%) than in those with HKAA >170° (0.35%). Conclusion: Increased mLDFA and MA-AA values were associated with more severe varus deformity (showed reduced HKAA values), indicating a need to individualize distal femoral valgus correction during TKA for patients with severe varus deformity. Preoperative mLDFA assessment may optimize alignment and surgical outcomes.